2019
DOI: 10.3390/plants8120568
|View full text |Cite
|
Sign up to set email alerts
|

Trehalose Protects Maize Plants from Salt Stress and Phosphorus Deficiency

Abstract: This study is undertaken to elucidate the role of trehalose (Tre) in mitigating oxidative stress under salinity and low P in maize. Eight-day-old maize seedlings of two maize varieties, BARI Hybrid Maize-7 and BARI Hybrid Maize-9, were subjected to salinity (150 mM NaCl), low P (5 µM KH2PO4) and their combined stress with or without 10 mM Tre for 15 d. Salinity and combined stress significantly inhibited the shoot length, root length, and root volume, whereas low P increased the root length and volume in both … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 68 publications
5
24
0
Order By: Relevance
“…These decreases were correlated with significant increases in total phenolic contents as compared with untreated plants. A similar positive impact of trehalose was recorded in maize plants exposed to salt stress by increasing the growth parameters and photosynthetic activity of the plant (Rohman et al, 2019).…”
Section: Physiological Responsesupporting
confidence: 70%
“…These decreases were correlated with significant increases in total phenolic contents as compared with untreated plants. A similar positive impact of trehalose was recorded in maize plants exposed to salt stress by increasing the growth parameters and photosynthetic activity of the plant (Rohman et al, 2019).…”
Section: Physiological Responsesupporting
confidence: 70%
“…MDA is the final product of membrane lipid peroxidation, and its content can reflect the extent to which plants suffer from adversity damage ( Wen et al, 2012 ). Previous studies found that the MDA content increased significantly under temperature stress and phosphorus stress ( Rohman et al, 2019 ; Xia et al, 2021a ). This experiment found that the MDA content significantly increased under low-phosphorus stress and root zone high temperature, and the root zone high temperature treatment is more obvious, indicating that the membrane lipid peroxidation is obvious.…”
Section: Discussionmentioning
confidence: 92%
“…In fact, MG itself may serve as a stress signal in various organisms. In plants, for example, intracellular MG increases in response to drought (126,127), salinity (126,(128)(129)(130)(131), cold stress (126), heavy metals (128), or phosphorous deficiency (131), and overexpression of certain genes involved in MG detoxification has been shown to enhance salt tolerance in tobacco (126) and in Brassica juncea (132). Investigating whether MG detoxification is linked to abiotic stressors such as salt, temperature, or desiccation in Candida species would be an interesting avenue of future research, particularly in C. auris due to its persistence on hospital surfaces and high salt tolerance.…”
Section: Discussionmentioning
confidence: 99%